Legal Standards for Physical Therapy Tele-Rehabilitation: Authority, Consent, Medical Records, Personal Data - Widodo, Nanang Saputro Agung; Herisasono, Adi; Khayru, Rafadi Khan (Journal of Social Science Studies, 2024)
Tele-rehabilitation physiotherapy has developed as a form of electronic-based rehabilitation service that expands access and accelerates therapeutic communication. Changes in the service medium have given rise to the need for legality parameters that ensure services remain safe, orderly, and verifiable. This article examines the formulation of legal standards for tele-rehabilitation from the perspectives of professional authority, consent to treatment, and medical record keeping, and establishes parameters for legal accountability and health data protection in the relationship between patients, physiotherapists, and platform providers. The method used is normative jurisprudence with qualitative literature studies and thematic synthesis of health norms, electronic system norms, personal data protection norms, consumer protection norms, and civil contract principles. The results of the review show that tele-rehabilitation authority is vested in physiotherapists who are registered and licensed to practice, and who are required to work in accordance with physiotherapy service standards and SOPs that are adaptive to remote services. Consent for tele-rehabilitation is understood as a communication process that provides information about the objectives, procedures, risks, alternatives, limitations of remote services, and referral procedures, then stated in an electronic form that meets the requirements of a valid agreement and can be proven. Service records must be kept through medical records, including electronic medical records that guarantee integrity, security, confidentiality, and traceability of changes. In a tripartite relationship, the physiotherapist’s responsibility centers on clinical standards of care, while the platform’s responsibility centers on system reliability, security, and data processing for legitimate purposes. Health data protection is established through explicit consent, purpose limitation, data minimization, access control, incident notification, and fulfilment of data subject rights. Remedies include administrative sanctions, civil claims for damages, and the application of criminal provisions for certain violations. This article emphasizes the need for a clear division of roles between clinical service providers and technology providers, as well as documentation and security designs that strengthen legal certainty for all parties.